Dopady zavedení eura na hospodaření firmy - Hrabec, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská)
Diplomová práce analyzuje dopady zavedení eura na hospodaření vybrané firmy. Vstup České republiky do měnové unie se projeví pozitivními a negativními změnami, které budou působit na všechny subjekty v ekonomice. V práci jsou tyto dopady rozebrány a je určen jejich očekávaný výsledný efekt na zvolený podnik. Závěr práce je zaměřen na zhodnocení dopadů jednotné měny na firmu, identifikaci hlavních rizik spojených s nutnou transformací a navržení doporučení, která firmě pomohou k úspěšnému přechodu na euro.

This master's thesis analyzes the impact of euro implementation on corporation finance of a particular company. Czech Republic's accesion to the monetary union will entail positive and negative changes that will affect all entities in the economy. In this thesis, these impacts are analyzed and their expected net effect on the company is determined. The conclusion is focused on the evaluation of the impact of the single currency on the company, identification of the main risks associated with the necessary transformations and suggestion of the recommendations that will help the company to a successful transition to the euro.
Impact of Euro Implementation on Corporation Finance
Keywords: Euro; dopad; zavedení; měnová unie; hospodaření firmy; Euro; impact; implementation; Monetary Union; corporate finance